Musculoskeletal Disorders in Agriculture: A Review from Web of Science Core Collection - Manuel Barneo-Alcántara; Manuel Díaz-Pérez; Marta Gómez-Galán; Ángel Carreño-Ortega; Ángel-Jesús Callejón-Ferre (Agronomy, 2021)
Agricultural workers suffer from many work-related illnesses. Some of the most common include musculoskeletal disorders (MSDs). These types of disorders are caused by diverse factors. This research study intends to demonstrate the worldwide concern for MSD in agriculture. The objective is to compile and recognize in detail all the available studies on musculoskeletal disorders in agriculture developed in the world and by countries in the last 26 years. The Web of Science database was used for this purpose. Two hundred and fifty-six documents were found, of which 221 were finally selected for inclusion in the study. The studies span a period from 1995 to 2020. Of these, studies that were linked to improving sustainability stood out. Most of the research of this type emanates from developed countries. The conclusions to be drawn are that few countries pay attention to this area and that preventive measures are insufficient. Mechanization and improvement in work methods and organization are methods to reduce risks.